Writing´s process through Research in the Basic Secondary´s Students of the rural area in the Department of Nariño, Colombia - Gómez Zambrano, Sandra Jeraldine (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
To improve the writing skills through research-based learning in Basic Secondary students are presented in this article. The relationship between the writing models and the research-based learning contribute to find the way to propose questions based on the connection between the school and rural territories, where research is the fertile field for writing.